2022
DOI: 10.3390/polym14225042
|View full text |Cite
|
Sign up to set email alerts
|

Development of Smart Bilayer Alginate/Agar Film Containing Anthocyanin and Catechin-Lysozyme

Abstract: Smart packaging can provide real-time information about changes in food quality and impart a protective effect to the food product by using active agents. This study aimed to develop a smart bilayer film (alginate/agar) with a cellulose nanosphere (CNs) from corncob. The bilayer films were prepared using 1.5% (w/w) sodium alginate with 0.25%% (w/v) butterfly pea extract incorporated (indicator layer) and 2% (w/w) agar containing 0.5% (w/v) catechin–lysozyme (ratio 1:1) (active layer). The CNs were incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Recently, many researchers have suggested adding LY as a preservative to extend the shelf life of food and medicines ( Zhang and Rhim 2022 ). Romruen et al, (2022) developed a smart bilayer film (alginate/agar) containing 0.5% (w/v) catechin-lysozyme, the film possessed exceptional antibacterial and antioxidant activities. The results of the study showed that smart bilayer films containing LY extend the shelf life of food effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have suggested adding LY as a preservative to extend the shelf life of food and medicines ( Zhang and Rhim 2022 ). Romruen et al, (2022) developed a smart bilayer film (alginate/agar) containing 0.5% (w/v) catechin-lysozyme, the film possessed exceptional antibacterial and antioxidant activities. The results of the study showed that smart bilayer films containing LY extend the shelf life of food effectively.…”
Section: Introductionmentioning
confidence: 99%